(untitled) (International Journal of Food and Nutritional Sciences, 2022)
India is the second largest country in the world based on population and a major part of the population are depends on agricultural activities. Agriculture plays a predominant role in the economic development of a country. More than 70% of the people engaged in agricultural activities in India. So, agriculture is the backbone of our country. It also provides some raw materials for industrial sector also. For example, cotton, sugarcane, Jude, is the major raw materials for the textiles and sugar industry. In The present study is focused on the production of banana and paddy cultivation and it has been carried out with the sample size of 120 farmers randomly for primary data collections.